A new world map in textiles and clothing : adjusting to change. - Safadi, Raed, 1958-; Audet, Denis (OECD, 2004)
The World Trade Organization Agreement on Textiles and Clothing led to the termination of quantitative restrictions at the end of 2004. Under the agreement, countries will no longer be able to protect their own industries by means of restrictions on imports of textile and clothing products. Where will jobs be lost and new markets found, and how can governments help their own textile and clothing industries adjust to this new trade regime?